DESIGN OF A MINIATURE SINGLE-PHASE TRANSMISSION SYSTEM ON ELECTRIC POWER SYSTEMS - Dwinanto, Bambang; Harianto, Bambang; Yulianto, Bambang (INFOKUM, 2022)
The miniature transmission system is part of the electric power system that functions as a channeler of electrical power from the power generation system to the distribution system through substations. The electrical power is flowed by a copper conductor that has good conductivity. Transmission lines are installed in the air using towers as support for conducting cables. This miniature transmission system works on a small scale and serves to explain how the real transmission system works. The purpose of designing this tool is to test the magnitude of the voltage drop and power loss on each line. The line voltage drop can be obtained by calculating the voltage difference on the send and receive side of the transmission line. Meanwhile, to find the power loss on each line is to find the value of the conducting resistance and current on each of its lines.